2005
DOI: 10.1021/jm050418d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationship of the First Nonpeptidergic Inverse Agonists for the Human Cytomegalovirus Encoded Chemokine Receptor US28

Abstract: US28 is a human cytomegalovirus (HCMV) encoded G-protein-coupled receptor that signals in a constitutively active manner. Recently, we identified 1 [5-(4-(4-chlorophenyl)-4-hydroxypiperidin-1-yl)-2,2-diphenylpentanenitrile] as the first reported nonpeptidergic inverse agonist for a viral-encoded chemokine receptor. Interestingly, this compound is able to partially inhibit the viral entry of HIV-1. In this study we describe the synthesis of 1 and several of its analogues and unique structure-activity relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Since CX3CL1/Fractalkine functions as an acute agonist for calcium but as an inhibitor of PLC-␤ activity, it will be interesting to determine whether the US28 inhibitor VUF2274 also functions in a similar manner. Nonetheless, it will be important to more fully examine the effects of CX3CL1 and VUF2274 on a wide variety of signaling activities prior to investigating whether these US28 "inhibitors" could be used as models for potential novel drug design (7,22). Our results clearly indicate that US28 can constitutively turn on PLC-␤ signaling activity but also indicate that this signaling is not necessarily transduced downstream to effectors such as calcium unless agonist is present.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Since CX3CL1/Fractalkine functions as an acute agonist for calcium but as an inhibitor of PLC-␤ activity, it will be interesting to determine whether the US28 inhibitor VUF2274 also functions in a similar manner. Nonetheless, it will be important to more fully examine the effects of CX3CL1 and VUF2274 on a wide variety of signaling activities prior to investigating whether these US28 "inhibitors" could be used as models for potential novel drug design (7,22). Our results clearly indicate that US28 can constitutively turn on PLC-␤ signaling activity but also indicate that this signaling is not necessarily transduced downstream to effectors such as calcium unless agonist is present.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, deletion of this domain could alter normal agonist-induced trafficking patterns and therefore would appear to be resistant to the inhibitory effects of CX3CL1. It will be interesting to assess the function of the recently described US28 small molecule inhibitor VUF2274 in its regulation of US28 induced calcium signaling and to determine whether this is influenced by the carboxy-terminal region (7,22). Since CX3CL1/Fractalkine functions as an acute agonist for calcium but as an inhibitor of PLC-␤ activity, it will be interesting to determine whether the US28 inhibitor VUF2274 also functions in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, CC chemokines such as CCL2 and CCL5 do not seem to affect the basal activity of US28 signaling. They rather seem to act as neutral antagonists for GPCRs-mediated signaling (Arvanitakis et al ., 1997; Hulshof et al ., 2005). It was also found that activation of Rho and FAK only occurs via Gα 12/13 following chemokine binding to US28 (Billstrom et al ., 1998; Gao and Murphy, 1994; Melnychuk et al ., 2004; Streblow et al ., 2003) (Fig.…”
Section: Host Signaling Pathways Regulated By Us28mentioning
confidence: 99%
“…Besides inhibiting US28-mediated signaling activity in transfected cells, VUF2274 could also reduce the constitutive activity of US28 observed in HCMV-infected cells [33]. Such inverse agonist compounds may be promising antiviral drugs, but further optimization and improvement of the affinity of these compounds is still required [60,61].…”
Section: The Rhadinovirus Genus: Hhv-8/kshvmentioning
confidence: 99%